Transformation of Aesthetic Preferences: Legitimate Taste in Performing Arts on Social Media - Arif Eko suprihono (Institut Seni Indonesia Yogyakarta, 2025)
This article is the result of research on the phenomenon of the transformation of aesthetic preferences among internet users toward stage performing arts. Digital citizens are a new form of entity, born from the development of social media technology. One of the effects of the interaction between social media and performing arts is the emergence of a new virtual stage format to meet the aesthetic needs of internet society. There has been a transformation where live stage performances have taken on digital form through the involvement and creativity of cinematography technology. The issue that arises concerns which factors can consistently be maintained in performing arts uploads as a form of media transformation and its models of appreciation. This research uses netnography and hermeneutics methods. The issue of the aesthetic transformation of performing arts is found in the form of internet data. By using digital responsive sentiment data, the researcher identifies and analyses netizen sentiment. As netizen appreciation differs in form and aesthetic enjoyment, this study demonstrates an extreme shift in preferences. The research findings will be presented in the form of a narrative report and the ideas disseminated through scientific journals community.Key words: performance transformation, aesthetic preferences, legitimate taste, social media uploads.